The Function of Intrinsic Motivation in Driving Self-Efficacy for Fraud Detection - Amlayasa, Anak Agung Bagus; Sanjaya, I Gusti Ngurah; Pamungkas, Imang Dapit; Komaludin, Ade; Darma, Dio Caisar (International Journal of Accounting and Economics Studies, 2025)
Fraud detection in audit practice faces significant challenges because the implementation of auditor duties can be influenced by psychological ‎aspects such as self-efficacy and intrinsic motivation. This research aims to examine how self-efficacy affects an auditor’s ability to detect ‎fraud and the role of intrinsic motivation as a mediator in this relationship. A survey method was employed using a questionnaire distributed ‎via Google Forms. The sample consisted of 104 auditors from various Public Accounting Firms (KAP) in Indonesia. Purposive sampling ‎was employed, involving 104 auditors with relevant qualifications and experience who were deliberately selected to enhance the credibility ‎of the data collected, as they were deemed most capable of providing information pertinent to the study’s focus. Empirical findings reveal ‎that self-efficacy significantly influences intrinsic motivation; however, self-efficacy alone has an insignificant direct impact on fraud detection. Interestingly, intrinsic motivation has a significant effect on fraud detection. Implicitly, self-efficacy influences fraud detection indirectly through intrinsic motivation. The implications of this research underscore the importance of developing training programs that enhance ‎both self-efficacy and intrinsic motivation, enabling auditors to perform their duties more responsibly. Future research should consider expanding the existing literature by integrating psychological perspectives to better understand auditor behavior. Discussions on the upcoming ‎agenda concerning the implementation of other schemes by increasing sample size and expanding the scope of observation—taking into ‎account various regulations and cultural contexts—will enhance practical insights‎.